The Identity of New People in Darcy Ribeiro's Work Brazilian People - de Melo Costa Junio, Omundsen; Nery Carneiro, Éverton (Technium Social Sciences Journal, 2023)
The present research explores Darcy Ribeiro's contributions about the identity of the Brazilian people, which emerges as an identity of new people, as something that previously had no parallels, since it is the result of the historical processes of colonization and miscegenation. In this sense, this article uses basic research, based on a qualitative approach, with a search through bibliographical research, to try to understand the identity of a people who went through a process of not recognizing themselves as Portuguese, nor black African and nor indigenous, which is born from the harsh violence provoked at the beginning of the history of terra brasilis, when the colonizers arrived. Key concepts and even Darcy Ribeiro's own bibliography are explored in order to understand the notions of identity, culture, education, emancipation and construction of the Brazilian People. It is assumed, above all, that the Brazilian people, who are not the result of a racial democracy, but of the intersection of the white Portuguese, black African and indigenous matrices originating in the land of Brazil, demanding action in favor of the integration of all these people in the scope of educational training, citizen recognition and the realization of their prerogatives of dignity - in contrast to exclusion and inequalities.